Przegląd Informacyjny (Komitet Biotechnologii PAN, 1993)
Keywords: biotechnologia

Genetyka i zrozumienie życia - Twardowski, Tomasz (Komitet Biotechnologii PAN, 1993)
Keywords: biotechnologia

Pierwsza pełna sekwencja chromosomu eukariotycznego (Komitet Biotechnologii PAN, 1993)
Nowości
Keywords: biotechnologia

Charakterystyka aktywności katalitycznej acylazy penicylinowej w formie wolnej i stabilizowanej - Bryjak, Jolanta; Noworyta, Andrzej (Komitet Biotechnologii PAN, 1993)
Three different enzyme preparations were investigated: native enzyme, enzyme stabilized byadding poly(ethyleneimine) and enzyme attached to acrylic carrier. The preparations were compared with regard to their storage, temperature and pH-stabilities as well as the effect of temperature and pH-value on enzyme activity. It was found that for all preparations hydrolysis waskinetically limited. Five kinetic equation constants were calculated. The enzyme stabilized bypoly(ethyleneimine) was selected as the best preparation to be applied in industry.
Keywords: biotechnologia

Bioutylizacja modelowego ścieku przemysłu mleczarskiego w fermentorach laboratoryjnych różnej konstrukcji - Michalski, Henryk; Jamroz, Teresa; Sencio, Barbara (Komitet Biotechnologii PAN, 1993)
The purpose of the study was to determine the effect of the fermenter construction on theutilization of model dairy waste. The process was carried out using K.Jragilis at controlled pHand temperature. The bioutilization process was performed in the fermenter FL-10 equippedwith three different mixing systems with baffles and without them. A circulating stirrer withdiffuser (A, B), a stirrer with rotating helical strips (C, D) and two turbine-disc impellers mountedto a common shaft (E, F) were used. The process was investigated at the aeration rate Wm=1.0and two rotation frequencies of the stirrer shaft: 450 min'^ and 650 min"^The optimal results were obtained by using A and B systems.
Keywords: biotechnologia

Próba granulacji osadu czynnego w procesie ciągłej fermentacji metanowej - Wieczorek, A.; Michalski, H. (Komitet Biotechnologii PAN, 1993)
The development of granular sludge in the UASB reactor was investigated in bench scale(6,48 dm^). The different substrate loading rates were used during experiment. A syntheticmedium based on volatile fatty acid was used. Digested sewage sludge from distillery wastewatertreatment plant was used as a seed. The granules of ea. 0,5 mm diameter had developed afterabout 120 days of operation. The settling rate of these granules was 20 - 50 m/h.
Keywords: biotechnologia

Negatywne zjawiska w nauce - Szymański, Maciej; Barciszewski, Jan (Komitet Biotechnologii PAN, 1993)
In this paper we are discussing some ethical aspects of scientific research. We have focusedon various forms of scientific fraud and its possible consequences for scientific community andfor the relationships with the public. Despite more and more examples of scientific fraud,especially in biomedical sciences, we believe that it is only marginal problem and that scientificcommunity can find a way to solve it.
Keywords: biotechnologia

Krystalizacja kwasów nukleinowych - Adamiak, Dorota A. (Komitet Biotechnologii PAN, 1993)
Crystallization is the most important and challenging step in the determination of the structure of biomolecules and macromolecules by diffraction methods.Macromolecules are extremely complex physical-chemical system whose properties vary as afunction of many environmental influences such as temperature, pH, ionic strength and solventcomposition. Therefore, a number of factors influencing macromolecule crystal growth ought tobe considered. Despite of considerable interest in the approaches allowing for continuous monitoring and setting of crystal growth conditions, in practice, numerous trials ought to be performedin order to obtain appropriate crystals characterized by their optimal geometrical parameters,crystallographic symmetry, unit cell and, most importantly, their high resolution.The vapour diffusion and the microdialysis methods are discussed as the most widely usedcrystallization methods of macromolecules.
Keywords: biotechnologia

Selenocysteina — 21. aminokwas uniwersalnego kodu genetycznego - Pawełkiewicz, Jerzy (Komitet Biotechnologii PAN, 1993)
Biosynthesis and properties of selenocysteine — 21®*^ amino acid of the diverse genetic codeare discussed. New structural pecularities of Sec-tRNA^®'' as mRNA are crucial for incorporationof selenocysteine into some proteins. Pseudoknot structure can be formed within mRNA andplay a regulatory role in translation.
Keywords: biotechnologia

Zastosowanie technik biologii molekularnej w diagnostyce chorób genetycznych - Słomski, Ryszard; Kwiatkowska, Jolanta; Chlebowska, Hanna (Komitet Biotechnologii PAN, 1993)
Following the initial reports of the cloning of a DNA fragment, modem molecular geneticsfound immediate practical application in molecular analysis and diagnosis of human diseases.Genomic DNA, RNA, nucleic acids from archival specimens or cloned DNA may be startingmaterials for gene analysis. In extreme cases complete analysis can be performed on the DNAfrom a single cell or a few microdissected chromosome fragments, or on RNA from only fewcells. Many variations of the basic analytical procedures have now been described and appliedto a range of medical disciplines. These include, the polymerase chain reaction (PCR), whichhas had a major impact on the diagnosis and screening of genetic diseases and cancer, therapid detection of fast or slow growing microorganisms and vimses, such as mycobacteria andHfV, the detection of minimal residual diseases in leukaemia and in HLA typing. The analysisof archival and forensic material has applications in forensic pathology and evolutionary biology.PCR technique has also established a central role in the human genome project.
Keywords: biotechnologia

Budowa niektórych genów organelli roślinnych - Augustyniak, Halina (Komitet Biotechnologii PAN, 1993)
Some of the organellar genes contain introns. Most of genes possessing introns in higherplants contain single introns. Introns found in chloroplast genes can be classified into threegroups based on their structures. The largest group includes introns which can be folded intoa secondary structure similar to the postulated structure of group II introns in fungal mitochondrial genes.
Keywords: biotechnologia

Flow of genetic material - Dixon, Bernard (Komitet Biotechnologii PAN, 1993)
Keywords: biotechnologia

Novo Nordisk’ response to the new market-driven environmental demands - Kingo, Lise (Komitet Biotechnologii PAN, 1993)
Keywords: biotechnologia

Kształcenie biotechnologów w Polsce - Grajek, Włodzimierz (Komitet Biotechnologii PAN, 1993)
In the 1980s biotechnology was included in the curricula of Polish universities and polytechnics. At the moment there are over 7 hundred students of biotechnology related faculties.Food and environmental biotechnology is the most popular specialization in biotechnologicaleducation. However, relatively few students continue their studies at the Ph.D. level.
Keywords: biotechnologia

Odbiór społeczny biotechnologii w Polsce - Suchocka, Renata; Suchocki, Bolesław; Tittenbrun, Jacek (Komitet Biotechnologii PAN, 1993)
Badania odbioru społecznego biotechnologii nie mają długiej tradycji w naszym kraju. W artykule przedstawiono pierwsze polskie badania socjologiczne przeprowadzone na studentachi uczniach szkół średnich. Prace wykazały wysoką akceptację społeczną biotechnologii przy bardzo niewielkiej znajomości merytorycznej problemu.
Keywords: biotechnologia

Działania grup eksperckich OECD w zakresie bezpieczeństwa w biotechnologii - Ilnicka-Olejniczak, Olga (Komitet Biotechnologii PAN, 1993)
Organizacja Ekonomicznej Współpracy i Rozwoju (OECD) podjęła działania w zakresie biotechnołogii w 1981 r. Dotyczą one w szczególności analizy trendów rozwojowych, bezpieczeństwapracy, ochrony własności intelektualnej oraz środowiska.
Keywords: biotechnologia

Biozagrożenia i biobezpieczeństwo - Chmiel, Aleksander (Komitet Biotechnologii PAN, 1993)
The development of techniques of DNA recombination in vitro is a basis for the discussionon biohazard cind biosafety in laboratory experiments, technological processes and for the environment. After twenty years of experience in this field no hazardous incident was publishedand therefore we claim that genetic engineering is safe.
Keywords: biotechnologia

Polska biotechnologia w relacji do Europejskiej Federacji Biotechnologii - Bielecki, Stanisław (Komitet Biotechnologii PAN, 1993)
Przedstawiono polskie organizacje i towarzystwa naukowe prowadzące działalność w zakresiebiotechnologii, szczególnie we współpracy z Europejską Federacją Biotechnologii (EFB); omówionoich strukturę organizacyjną oraz scharakteryzowano inicjatywy naukowe.
Keywords: biotechnologia

Prawna ochrona zasobów genowych w Polsce - Kasprzak, Krzysztof (Komitet Biotechnologii PAN, 1993)
The Law on protecion of nature includes regulations concerning legal bases for protecion ofbiodiversity and gene resources. It results in tasks for local authorities with regard to ecologicaleducation of the society. Implementation of the law is now their responsibility.
Keywords: biotechnologia

Własność intelektualna w biotechnologii: ochrona naturalnych zasobów genomowych oraz własność danych genetycznych - Twardowski, Tomasz (Komitet Biotechnologii PAN, 1993)
Prawa własności intelektualnej chronione przez patenty, prawa autorskie czy nawet „sekretyfirmy” nie wyjaśniają problemów związanych z własnością danych analitycznych pozyskiwanychz zastosowaniem nowoczesnych technik analizy genomu człowieka czy też nie zabezpieczają kwestii własności naturalnych zasobów genetycznych. Ilustracje z aktualnych prac badawczych i działań politycznych w skali międzynarodowej ilustrują znaczenie tych kwestii, zarówno w aspekciemoralnym jak i ekonomicznym. Zagadnienia te są przedstawione w artykule, aczkolwiek obecnystan prawny uniemożliwia przedstawienie konstruktywnych rozwiązań.
Keywords: biotechnologia

Ochrona osiągnięć biotechnologicznych - Roden, Lutz van (Komitet Biotechnologii PAN, 1993)
W artykule przedstawiono sytuację prawną w zakresie ochrony osiągnięć biotechnologicznychprzez patenty oraz ochronę odmian roślin. Omówione zostały podstawy prawne systemu ochronywłasności intelektualnej w Niemczech (z krótkim rysem historycznym) oraz perspektywy.
Keywords: biotechnologia

Ochrona patentowa wynalazków z dziedziny biotechnologii w Polsce - Stefani-Iwanow, Danuta (Komitet Biotechnologii PAN, 1993)
Keywords: biotechnologia

Perspektywy biotechnologii - Houwink, Eric H. (Komitet Biotechnologii PAN, 1993)
Autor przedstawia problematykę dotyczącą rozwoju nowoczesnej biotechnologii w perspektywie do roku 2000.Wiele miejsca poświęca analizie rynku zbytu produktów biotechnologicznych w aspektach:wartości finansowych, prawnych, bezpieczeństwa oraz odbioru społecznego.
Keywords: biotechnologia

Biotechnologia w Polsce - Stec, Wojciech J. (Komitet Biotechnologii PAN, 1993)
W artykule przedstawiono definicje biotechnologii oraz osiągnięcia „nowoczesnej biotechnologii, która jest podmiotem artykułu. Nakreślono stan ekonomiczny nauki polskiej, a na tym tlebiotechnologii i nauk probiotechnologicznych. Zaproponowano kierunki rozwoju biotechnologii wPolsce.
Keywords: biotechnologia

Editorial (Komitet Biotechnologii PAN, 1993)
Keywords: biotechnologia